Subpar parks : America's most extraordinary national parks & their least impressed visitors - Share, Amber (Plume, Penguin Random House LLC, 2021)
"Based on the wildly popular Instagram account, Subpar Parks features both the greatest hits and brand-new content, all celebrating the incredible beauty and variety of America's national parks juxtaposed with the clueless and hilarious one-star reviews posted by visitors"--